Terapan Ornamen Geometris Jepara Pada Meja Kerja Guru Di SMK Hasan Kafrawi Jepara - Ridhwan, Muhammad; Wibowo, DS Drajad; Agus Susila, Dwi (Besaung : Jurnal Seni Desain dan Budaya, 2025)
The teacher's work desk is an important element in the learning environment which functions as a place to work and interact with students. However, often the tables used do not pay attention to aspects of use, ergonomics and aesthetics. In designing work desks, vocational school teachers use design studies, namely the Design Thinking method. Not only aspects of use and ergonomics, the author also pays attention to aesthetics, namely by adding elements of Jepara Geometric Ornaments as a cultural aesthetic value aimed at combining traditional beauty with practical functions in an educational environment. Jepara's geometric ornaments, such as the Kawung motif, have deep historical roots and are often used in traditional wood carvings. This motif symbolizes balance and harmony, which is in accordance with educational values. Its application in the design of the teacher's work desk not only adds aesthetic value, but also connects the learning space with local cultural heritage. It is hoped that the design of the teacher's work desk with elements of Jepara geometric ornaments as a cultural aesthetic value can create a learning environment that is different from others, more beautiful, comfortable, and pays attention to cultural values ​​and preserves local cultures.